Clinically elevated depression scores do not produce negative attentional biases in caregivers of autistic children - Lovell, Brian; McCarty, Kris; Penfold, Phoebe; Wetherell, Mark A. (Frontiers in Psychiatry, 2023)
Objective Depression scores in caregivers of autistic children often fall in the clinical range. The attention of clinically depressed individuals tends to be biased toward negatively toned information. Whether caring for an autistic child might also be characterized by a negative attentional bias was explored here. Methods A sample of N = 98 (57 caregivers and 41 controls) completed questionnaires assessing depressive symptoms. Orienting attention to (i.e., vigilance), and shifting attention away from (i.e., disengagement), negative information was assessed via an online version of the emotional face dot probe task. Results Mean depression scores in caregivers, falling in the borderline clinical range, were significantly higher compared with controls. Groups, however, were indistinguishable with respect to vigilance and disengagement, and these attentional indices were unrelated to depression scores. Conclusion Caring for an autistic child, while associated with borderline clinical depression scores, was not characterized by a negative attentional bias. Findings are discussed in the context of methodological shortcomings and recommendations for future research.